Immersive Virtual Reality Influences Physiologic Responses to Submaximal Exercise: A Randomized, Crossover Trial - Rutkowski, Sebastian; Szary, Patryk; Sacha, Jerzy; Casaburi, Richard (Frontiers in Physiology, 2021)
Background: Little is known about the use of virtual reality in the exercise capacity test, although attempts have been made to use VR systems during cycle ergometer training. However, the authors in in previous studies utilized a non-immersive VR. Objectives: This cross-sectional, randomly assigned study aimed to assess the influence of immersive virtual reality (VR) on exercise tolerance expressed as the duration of a submaximal exercise test (ET) on a cycle ergometer. Methods: The study enrolled 70 healthy volunteers aged 22–25 years. Each participant performed an ET with and without VR. Time- and frequency-domain heart rate variability (HRV) parameters were analyzed for the first 3 minutes (T1), the last 3 minutes (T2) and the time at which the shorter of the two tests terminated (Tiso). In the time-domain, a standard deviation of R-R intervals (SDNN) and a root mean square of successive R-R interval differences (RMSSD) in milliseconds were computed. The following spectral components were considered: low frequency (LF), high frequency (HF), total power (TP) and LF/HF ratio. The study was registered in ClinicalTrials.gov (NCT04197024). Results: Compared to standard ET, tests in immersive VR lasted significantly longer (694s vs. 591s, P<0.00001) and were associated with lower HR response across the range of corresponding exercise levels, averaging 5-8 beats/min. In the multiple regression analysis, the ET duration was positively determined by male sex, immersion in VR, and negatively determined by HRT1 and RMSSDT1. Conclusion: Exercising in VR is associated with lower HR which allowed subjects to exercise for a longer time before reaching target heart rate. In addition, the increase in exercise duration was found to be related to an adjustment in autonomic nervous activity at a given work rate favoring parasympathetic predominance.